Highlights of the third annual international altitude-training symposium - Pfitzinger, P. (Sportscience, 2000)
The third international symposium on altitude training was held at the High Altitude Sports Training Complex at Northern Arizona University, Flagstaff, on February 23-26, 2000. Author presents here a summary of the presentations on the physiology of altitude training (Robert Chapman), nutritional requirements of altitude training (Barry Braun), new approaches to altitude training (Randy Wilber), and the state of the altitude art (Ben Levine).